Murky world / Richard Corben, Mike Shields. - Corben, Richard (Dark Horse Books, 2023)
Tugat the warrior wakes from a strange dream only to find himself in a bizarre land populated by hungry deadlings, cruel necromancers, buxom cyclopes, evil cults, and more as he sets off on a dangerous journey with his beloved horse Frix.